2010
DOI: 10.1021/ma1011683
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ω-End Group Functionalized Poly(methyl methacrylate)s via RAFT Polymerization

Abstract: Living" poly(methyl methacrylate) (PMMA), prepared by the RAFT technique, reacted with maleic anhydride to give succinic anhydride-terminated PMMA (SA-PMMA) in very high yield. The ω-terminal anhydride residues react in high yields with primary alcohols, primary amines and aromatic amines. As examples, SA-PMMA reacted with 1H,1H,2H,2H-perfluorodecylamine to give a polymer containing 5.78% of fluorine; with Disperse Orange 3 to give a dye-labeled PMMA; with 9-hydroxymethylanthracene to give a fluorescently labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Sasso et al [18] reported the diazomethane methylation of a RAFT-synthesized polymer. However, the dithiobenzoate ends had been previously removed by amine treatment and no unexpected reactions were reported.…”
Section: The Reaction Between Diazomethane and Polymers With Dithiobementioning
confidence: 99%
“…Sasso et al [18] reported the diazomethane methylation of a RAFT-synthesized polymer. However, the dithiobenzoate ends had been previously removed by amine treatment and no unexpected reactions were reported.…”
Section: The Reaction Between Diazomethane and Polymers With Dithiobementioning
confidence: 99%
“…280 Finally, the addition maleic anhydride or maleimide at the end of the polymerization was proposed to give succinic anhydride or functional terminated polymers in very high yield, respectively. 281,282 The presence of this anhydride group can be exploited to react different alcohols, primary amines and aromatic amines with a very high functionality (75-95%). The polymer can be chain extended using another monomer to introduce mid-chain functionality.…”
Section: Chemical Modification Of the Z Group Of Raft Agentsmentioning
confidence: 99%
“…The thiol-functional polymers could be further modified with thiol-reactive reagents, such as maleic anhydride, 66 for creating highly reactive sites for conjugation with biomolecules. Alternatively, thiol-functional polymers can be used directly for bioconjugations without any further modification.…”
Section: Post-polymerization Bioconjugation Strategymentioning
confidence: 99%
“…When designing R-and Z-groups, amines, thiols, carboxylic acids and ketones/aldehydes, which are the reactive groups of biological molecules, commonly used for bioconjugations, have been considered. 56,66,69,70, Bioconjugation strategies combining click reactions such as azidealkyne cycloadditions and thiol-ene additions with end-group functionalized RAFT polymers have also attracted attention because of high efficiency of such reactions (vide infra).…”
Section: Post-polymerization Bioconjugation Strategymentioning
confidence: 99%